Where are the sleeping beauties and princes in educational technology journals?. Issue 4 (20th December 2017) - Huang, Tien-Chi; Jeng, Yu-Lin; Hsu, Chieh; Lai, Chin-Feng
Abstract : Purpose: The purpose of this paper is to introduce an affective computing-based method of identifying sleeping beauties and their princes in five educational technology journals. Design/methodology/approach: This study develops an information technology-based methodology to analyze sleeping beauties in the field of educational technology. The authors seek to determine the characteristics of studies which trigger the awakening of sleeping beauties (called "princes"). The keywords and Hirsch index (H-index) are used as two essential analysis indicators. Findings: Between 2000 and 2015, these five journals included 7, 864 articles with a total of 77, 700 citations and 24, 312 keywords. This study identified articles as being in deep sleep (75.7 percent), less deep sleep (14.7 percent), and awakening (5.5 percent) states. According to the analytical results, 431 of 7, 864 articles are qualified as "sleeping beauties." Of the 431 sleeping beauties identified, 232 articles were awakened by trend princes, while 286 were awakened by H-index princes. A total of 128 sleeping beauties were awakened by both prince types. Besides, impact factors (IFs) of journals do not have a significant effect on the number of sleeping articles. Research limitations/implications: There are two main research limitations in this study. The first one is the amount of target journals. Only five well-known educational technology journals are analyzed in this research. There may be more valuable sleeping publications in other journals not been found. The second limitation is that the authors merely pick up the lead author of citing papers as the indicator to determine the H-index prince. The contributions of the rest of authors are not taken are not taken into consideration. These limitations should be further studied. Originality/value: To the knowledge, this study is the first one reporting the identification of sleeping beauty and princes in educational technology field. Furthermore, the authors devise an informational method to determine sleeping publications, sleeping beauty, and princes. A systematic analysis of five well-known journals in the field of educational technology field confirms the existence of "sleeping beauties." It is reported that improvements to a journal's IF are positively correlated to increased numbers of sleeping beauties being awakened. To reduce the number of such articles, or to reduce the overall sleeping duration, journal editors should not only seek to raise the journal's IF, but also strategically select keywords for maximum visibility, and promote articles to high H-index authors.